2008
DOI: 10.1161/hypertensionaha.107.099499
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction and the Development of Renal Injury in Spontaneously Hypertensive Rats Fed a High-Fat Diet

Abstract: Abstract-Obesity and hypertension have been identified as cardiovascular risk factors that contribute to the progression of end-stage renal disease. To examine the mechanisms by which a high-fat diet and hypertension contribute to endothelial dysfunction and renal injury, 8-week-old male spontaneously hypertensive rats and Wistar rats were fed a high-fat (36% fat) or a normal-fat (7% fat) diet for 10 weeks. The high-fat diet increased body weight in Wistar and hypertensive rats by 25 and 31 g, respectively. Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
96
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 48 publications
14
96
0
2
Order By: Relevance
“…As previously described, 19 total RNA was extracted from 50 mg of whole brain from male rats using the RNeasy lipid mini kit and DNase digestion (Qiagen, Valencia, CA) according to the manufacturer's protocol and RNA concentrations were determined using absorbance at 260 nm. Using RT 2 PCR array first strand kit (SuperArray Bioscience, Frederick, MD), 1 g of RNA was converted to cDNA.…”
Section: Real-time Polymerase Chain Reaction (Pcr) Apoptosis Gene Expmentioning
confidence: 99%
“…As previously described, 19 total RNA was extracted from 50 mg of whole brain from male rats using the RNeasy lipid mini kit and DNase digestion (Qiagen, Valencia, CA) according to the manufacturer's protocol and RNA concentrations were determined using absorbance at 260 nm. Using RT 2 PCR array first strand kit (SuperArray Bioscience, Frederick, MD), 1 g of RNA was converted to cDNA.…”
Section: Real-time Polymerase Chain Reaction (Pcr) Apoptosis Gene Expmentioning
confidence: 99%
“…29 SHR compared with Wistar Kyoto rats, for example, also gain less body weight in response to a chronic HFD. [30][31][32][33] To test our hypothesis, we exposed adult SHR to either a HFD or normal diet (ND) for 12 weeks. Before and during the dietary intervention, we assessed adiposity and measured 24-hour profiles of whole-body energy expenditure and energy intake.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies using an HF diet in SHR rats have addressed the question of whether this diet increases BP. [27][28][29] Twenty-four hours radiotelemetry measurements by Sevoda et al 28 found an increase in poststress BP and under unstressed active conditions during the dark night phase after 12 weeks of an HF diet. They concluded that dietary obesity promotes the development of nocturnal hypertension.…”
Section: Discussionmentioning
confidence: 99%